2009
DOI: 10.1001/archinternmed.2008.583
|View full text |Cite
|
Sign up to set email alerts
|

Abandonment at the End of Life From Patient, Caregiver, Nurse, and Physician Perspectives

Abstract: Background Surveys and anecdotes suggest that patients and family members sometimes feel abandoned by their physicians at the transition to end-of-life care. To our knowledge, no prior studies describe abandonment prospectively. Methods We conducted a longitudinal, qualitative study of patients, family caregivers, physicians and nurses using a community-based sample. Using a purposive recruitment strategy, we identified 31 physicians, who identified 55 patients with incurable cancer or advanced chronic obstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(98 citation statements)
references
References 21 publications
3
94
0
1
Order By: Relevance
“…2,28 The result may be the best of all possible outcomes-sensitive, respectful, and compassionate care for patients and survivors, and rewarding caregiving experiences for health professionals. 20,24,25 views expressed here do not necessarily reflect the position or policy of the Department of Veterans Affairs or the United States Government.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,28 The result may be the best of all possible outcomes-sensitive, respectful, and compassionate care for patients and survivors, and rewarding caregiving experiences for health professionals. 20,24,25 views expressed here do not necessarily reflect the position or policy of the Department of Veterans Affairs or the United States Government.…”
Section: Resultsmentioning
confidence: 99%
“…22 Doing so may promote closure for the grieving. 20,[23][24][25] Health professionals should also attend to beliefs such as those about the signs and duration of the time of death. As this study showed, different people may time death by different physiologic signs.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, the service provision by doctors to aged care facilities has been reported to be limited (Back et al, 2009;Gadzhanova & Reed, 2007;Watson, Hockley & Dewar, 2006;. A number of factors have been identified as contributing to a lack of service provision and a number of barriers have been identified that limit effective palliative care delivery by doctors to dying residents in residential aged care settings.…”
Section: Doctorsmentioning
confidence: 99%
“…For example, the impact of qualified professionals disconnecting with end of life care provision was highlighted by Back et al (2009), who conducted a longitudinal, qualitative study including "31 physicians, who identified 55 patients with incurable cancer or advanced chronic obstructive pulmonary disease, 36 family caregivers, and 25 nurses" (p. 475).…”
Section: The Federalmentioning
confidence: 99%
“…It is debated to what degree primary care physicians are involved in care at this time, as they are perceived as often transferring the care of the dying to specialists, especially for patients with cancer. [15][16][17] Studies attempting to measure this, however, have found considerable primary care physician involvement specifically for patients with terminal cancers. 17,18 The association between primary care physician involvement in end-oflife care and hospice referral is also debated.…”
mentioning
confidence: 99%